2011
DOI: 10.2337/dc11-0838
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Media Consumption Habits, Physical Activity, Socioeconomic Status, and Glycemic Control in Children, Adolescents, and Young Adults With Type 1 Diabetes

Abstract: OBJECTIVETo evaluate the relationship between media consumption habits, physical activity, socioeconomic status, and glycemic control in youths with type 1 diabetes.RESEARCH DESIGN AND METHODSIn the cross-sectional study, self-report questionnaires were used to assess media consumption habits, physical activity, and socioeconomic status in 296 children, adolescents, and young adults with type 1 diabetes. Clinical data and HbA1c levels were collected. Risk factors were analyzed by multiple regression.RESULTSYou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 25 publications
4
56
1
3
Order By: Relevance
“…Previous studies have shown that SES is associated with glycemic control and risk factors in type 1 diabetes (22)(23)(24)(25)(26)(27), but very few studies have examined how SES relates to CVD and death (7)(8)(9). These studies reported either a modest effect or no significant effect of SES or they were inadequately adjusted to allow for reliable inferences.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that SES is associated with glycemic control and risk factors in type 1 diabetes (22)(23)(24)(25)(26)(27), but very few studies have examined how SES relates to CVD and death (7)(8)(9). These studies reported either a modest effect or no significant effect of SES or they were inadequately adjusted to allow for reliable inferences.…”
Section: Discussionmentioning
confidence: 99%
“…Youth with T1D have reported a high duration of screen time per day, the typical proxy for sedentary behavior, ranging between 110 and 140 min per day of television watching, and between 40 and 255 min per day of computer use (Liese et al, 2013). In fact, in one study of youth with T1D, the average amount of accumulated screen time was 2.9 hr per day (Galler, Lindau, Ernert, Thalemann, & Raile, 2011), which exceeds the recommendation of less than 2 hr of screen time per day (American Academy of Pediatrics, 2001). Accelerometry was used in another study to assess intensity of activity in youth with T1D and it was found that 84% of recorded daily activity was in sedentary pursuits, thus potentially posing increased cardiovascular risks and poorer glucose control (Michaliszyn & Faulkner, 2010).…”
Section: Introductionmentioning
confidence: 86%
“…SES has been reported to have a serious impact on the prevalence of T1DM and T2DM as well as associated complications and mortality in every major ethnic group worldwide 1016. In order to determine the effect of SES and behavioral economics propensity on the progress of diabetic complications, in the present study, we conducted a survey among patients with diabetes using modified behavioral economics questionnaires, including those related to SES.…”
Section: Introductionmentioning
confidence: 99%